A Comparative Study of Cattle and Sheep Amoebiasis in Selected Regions of Baghdad City - Jebur, Lina A; Abbas, Athmar K (The Iraqi Journal of Veterinary Medicine, 2021)
This study was performed to microscopically detect the prevalence of amoebiasis in cattle and sheep fecal samples. One hundred fecal samples were collected from cattle and sheep from 3 completely different area in Baghdad city (Al-Tarmiyah, Al-Fudhaliyah, AbuGhraib). Our data recorded a total amoebiasis infection rate of 54% in cattle and 50% in sheep, without any significant differences between them. Males showed higher infection rates than females in cattle and sheep (62.5%) and (57.14) respectively. The difference between age groups with significant difference (P<0.01) were obtained in ages <1 year (72.7%) and (68.75%) in cattle and sheep respectively. This study has demonstrated the widespread of Entamoeba parasite in cattle and sheep in Baghdad city.